Integral sliding mode control of networked robotic manipulator: a dynamic event-triggered design. (17th January 2023) - Nath, Krishanu; Bera, Manas Kumar
Abstract : This paper addresses the trajectory tracking control of an uncertain robotic manipulator in a networked environment. To avoid the frequent usage of communication and computational resources and to maintain a robust tracking performance of the manipulator, an event-triggered integral sliding mode controller is designed. The controller comprises of a proportional-derivative feedback control loop for the control of the unperturbed /nominal system. The integral sliding mode controller is introduced to guarantee robustness by enforcing the sliding motion from the initial time instant eliminating the reaching phase. Further, to reduce the network usage, a dynamic triggering mechanism is incorporated to reduce the number of control updates. The controller gains are redesigned in an event-based framework to ensure the stability of the system. The closed-loop system with the proposed event-based control law is shown to exhibit Zeno-free behaviour, i.e. the triggering mechanism executes finite sampling instances in finite time. Simulation results are illustrated to prove the theoretical contributions along with the comparative analysis. GRAPHICAL ABSTRACT: UF0001